Mahyeldi-Audy Political Marketing Innovation During the Covid-19 Pandemic During the 2020 West Sumatra Regional Election - Rian Handika; Al Rafni (UIN Sunan Gunung Djati, 2022)
This study discusses the political marketing innovation of the Mahyeldi-Audy couple in the face of the 2020 West Sumatra Provincial Election during the Covid-19 period. The victory obtained by the Mahyeldi-Audy couple is a manifestation of the success of political marketing that has been carried out. This study aims to describe and analyze the political marketing strategy of the Mahyeldi-Audy pair in the 2020 West Sumatra gubernatorial election contestation. In researching the author, the author uses the theoretical framework of Niffenegger's 4P political marketing and Adman Nursal's 3P. This research is in the form of a qualitative descriptive. To obtain the data, it was obtained through in-depth interviews with the informants and coupled with a literature study which was then analyzed using theory. The results of this study indicate that the Mahyeldi-Audy pair runs a 4P marketing mix (product, promotion, place, and price). Strong political products can be seen from the figures, candidate backgrounds, vision and mission and work programs that are in accordance with the needs of the community. Effective promotions by both Mahyeldi-Audy and the winning team using push, pass, and pull marketing methods. The use of minimal material resources but with maximum results. Placement, mapping and segmenting voters as well as creating a good image and being able to place oneself at every level of society. The success of the Mahyeldi-Audy pair in winning the 2020 West Sumatra gubernatorial election was due to being able to design and execute a structured, creative and innovative political marketing strategy during the COVID-19 pandemic.